A importância do brincar na alfabetização e no letramento na educação infantil - Pereira, Emily Larissa Bortolott (Universidade Federal de São Carlos, 2025)
The paper entitled The Importance of Play in Literacy Development in Early Childhood Education investigates how playful practices are presented for the development of initial reading and writing skills in Early Childhood Education children. A bibliographic and qualitative research study analyzes the relationship between playing and learning. For this purpose, a bibliographic survey was carried out, from October to November 2024, in the Brazilian Digital Library of Theses and Dissertations (BDTD). From this survey, postgraduate works related to the proposed theme were selected and, still using official documents such as the National Common Curricular Base (BNCC), the National Curricular Guidelines for Early Childhood Education (DCNEI) and the Statute of the Child and Adolescent (ECA). The results indicate that playing is a central pedagogical tool, promoting not only cognitive and motor development, but also social, emotional and linguistic development. Singing games, storytelling, pretend play and activities involving sounds and rhymes are strategies that stimulate phonological awareness, creativity and interest in the world of literacy. In addition, the role of play in the development of children's autonomy, critical thinking and ability to express themselves is highlighted. However, the study also highlights challenges, such as the lack of teacher training to plan intentional playful activities and the pressure for early academic results, which can hinder the effective use of play in literacy. The research reinforces the need for public policies that value playfulness as a pedagogical strategy and guarantee the ongoing training of educators. It is concluded that playfulness is essential for meaningful and inclusive literacy, respecting the rhythm and particularities of each child. Playfulness should be understood as a right and a necessary practice in the daily routine of Early Childhood Education, promoting comprehensive development and preparing children for the challenges of Elementary School and life in society.
The importance of playing in literacy and literacy in early childhood education
Keywords: Brincar; Alfabetização; Letramento; Educação infantil; Práticas lúdicas; CIENCIAS HUMANAS::EDUCACAO::CURRICULO